2009
DOI: 10.1021/ol901334c
|View full text |Cite
|
Sign up to set email alerts
|

Phosphine-Mediated Olefination between Aldehydes and Allenes: An Efficient Synthesis of Trisubstituted 1,3-Dienes with High E-Selectivity

Abstract: The phosphine-mediated olefination of aldehydes with electron-deficient allenes to afford trisubstituted conjugated dienes in fair to excellent yields with high E-selectivity is described. The reaction represents a new reactivity pattern of allenes with aldehydes and also provides a highly stereoselective synthetic method for preparing conjugated dienes. In the reaction, the phosphine acts as a nucleophilic promoter to generate in situ an active phosphorus ylide which mediates the intermolecular olefination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…They demonstrated that triphenylphosphine could be used as the catalyst to isomerize γ -benzyl allenoate to the corresponding 2,4-dienoate in good yield. 179 Mechanistically, the initial addition of the phosphine occurs at the β -position of the γ -benzyl allenoate, resulting in the formation of the phosphonium dienolate 71 . After proton transfer, the vinylogous phosphonium ylide 72 is formed.…”
Section: Nucleophilic Phosphine Catalysis Of Allenesmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that triphenylphosphine could be used as the catalyst to isomerize γ -benzyl allenoate to the corresponding 2,4-dienoate in good yield. 179 Mechanistically, the initial addition of the phosphine occurs at the β -position of the γ -benzyl allenoate, resulting in the formation of the phosphonium dienolate 71 . After proton transfer, the vinylogous phosphonium ylide 72 is formed.…”
Section: Nucleophilic Phosphine Catalysis Of Allenesmentioning
confidence: 99%
“…In 2009, He and co-workers employed tertiary phosphines to promote internal ylide generation from γ -substituted allenoates (Scheme 672). 179 Employing the phosphonium ylide generated from nucleophilic addition of the phosphine to the allenoate, various functionalized diene systems were formed, exclusively with the E , E -configuration.…”
Section: Ylides Formed Through Nucleophilic Addition Of Phosphinementioning
confidence: 99%
“…7b,c,f The pioneering work by He and other researchers has demonstrated that allenoates and alkynoates also possess decent reactivity in stoichiometric phosphine-mediated olefination reactions with carbonyls. 18 In 2009, He and co-workers 19 disclosed a novel olefination reaction between c-substituted allenoates 19 and aldehydes under the mediation of phosphines such as PPh 3 or 1,3,5-triaza-7-phosphaadamantane (PTA), that provided trisubstituted 1,3-dienes 20 in high yields with exclusive E,E-selectivity (Scheme 10, eqn 1). Results indicated that the chemoselectivity was highly dependent on the nature of the c-substituent of the allenoates.…”
Section: Based On Electron-deficient Allene or Alkyne Substratesmentioning
confidence: 99%
“…通过叔膦与亲电性底物原位形成的烯丙基磷叶立 德具有丰富的反应性, 相关研究在近年来引起了化学家 浓厚的研究兴趣 [14] . 贺峥杰小组 [15] 和 Kwon 小组 [16] 值得一提的是, 与 γ-甲基联烯酸酯不同, γ-苄基或 γ-甲氧羰甲基联烯酸酯与醛或水杨醛反应时, 未能发生叔 膦催化的环化反应, 而是经原位形成的烯丙基磷叶立德 17 与醛的 Wittig 反应, 生成多取代共轭二烯烃(Scheme 10) [19,23] . 这种反应性的差异可能源于苯基或酯基的共 轭及立体位阻效应, 促使烯丙基磷叶立德 17 主要通过 α 位碳对醛进行亲核进攻, 从而发生经典的 Wittig 反应.…”
unclassified